Gene Expression 2022
DOI: 10.5772/intechopen.103013
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Elongation Factors in Health and Disease

Abstract: Gene expression is a complex process that establishes and maintains a specific cell state. Transcription, an early event during the gene expression, is fine-tuned by a concerted action of a plethora of transcription factors temporally and spatially in response to various stimuli. Most of the earlier research has focused on the initiation of transcription as a key regulatory step. However, work done over the last two decades has highlighted the importance of regulation of transcription elongation by RNA Pol II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 219 publications
(250 reference statements)
0
4
0
Order By: Relevance
“…AFF family proteins form SEC with p-TEFB, ELL, and EAF proteins to enhance the activity of RNA polymerase II and promote transcription elongation. 8 AFF proteins share functional domains including the N-terminal homology domain (NHD), AF4/LAF4/FMR2 homology domain (ALF), and the C-terminal homology domain (CHD) (Figure 1D). 7 The ALF domain promotes protein degradation while CHD is involved in dimerization and localization of the protein into puncta in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…AFF family proteins form SEC with p-TEFB, ELL, and EAF proteins to enhance the activity of RNA polymerase II and promote transcription elongation. 8 AFF proteins share functional domains including the N-terminal homology domain (NHD), AF4/LAF4/FMR2 homology domain (ALF), and the C-terminal homology domain (CHD) (Figure 1D). 7 The ALF domain promotes protein degradation while CHD is involved in dimerization and localization of the protein into puncta in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified a novel pathogenic variant (NM_001025108: c.2915G > C: p.Arg972Pro) in AFF3 in a Pakistani family with isolated syndactyly. AFF family proteins form SEC with p‐TEFB, ELL, and EAF proteins to enhance the activity of RNA polymerase II and promote transcription elongation 8 . AFF proteins share functional domains including the N‐terminal homology domain (NHD), AF4/LAF4/FMR2 homology domain (ALF), and the C‐terminal homology domain (CHD) (Figure 1D).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations